PENGARUH KENYAMANAN BERWISATA DAN PROMOSI PARIWISATA TERHADAP KUNJUNGAN WISATAWAN DI OBJEK WISATA HUTAN MANGROVE TONGKE-TONGKE - Amiruddin; Muhlis, Suardi; Wahid, Abd; Sandi (Program Studi Administrasi Publik, 2023)
Tongke-Tongke Mangrove Forest Tourism Object, Sinjai Regency has various attractions such as its biodiversity and natural beauty. Based on data from the Tourism Office, it is explained that the number of visits each year has increased, this is influenced by convenience and promotion. Therefore, to find out the magnitude of the influence of these two factors on the increase in the number of visits, this research was conducted. Determination of the sample was carried out using the slovin formula with a total of 140 respondents. The researcher used a questionnaire as a technique for collecting data and a Likert scale as a tool for measuring variables. The data analysis technique in this study used the SMART PLS 3.0 software tool. The results showed that the comfort of traveling and tourism promotion directly had a significant (real) effect on the number of visits